Experimental investigation on enhanced microscale heat transfer : fish scale channel - Aw, Wee Earn (2015)
The demand for effective methods for heat dissipation keeps increasing. Microchannel heat transfer technologies provide superior heat dissipation capability. However, it does have some challenges such as high manufacturing costs. Therefore, in this project, a microchannel test module which can be fabricated by conventional machining methods was utilised. The effect of Fish Scale channel profile on the heat transfer and flow characteristics of the microscale flow was experimentally investigated. In this project, the annular microchannel, of mean hydraulic diameter 0.6 mm, was formed by the outer surface of the insert and inner surface of the copper block. Two geometrical variables were proposed for the insert surface profile design, namely scale height to channel height ratio (e/H) and pitch length to scale height ratio (P/e). Experiments were conducted on seven types of microchannel profile under the conditions of flow rate 2 to 8 L/min and constant heat rate at 1000 W. Results show that the introduction of Fish Scale profile on microchannel had positive effect on the heat transfer performance in both geometrical variable designs. In the study of e/H, the highest average heat transfer coefficient was recorded at 34.5 kW/m^2·K. The results indicated that the larger the e/H ratio, the larger the average heat transfer coefficient of the microchannel profile. The percentage of enhancement in average heat transfer coefficient was around two times that of Plain profile at each Reynolds number for e/H= 0.7. In the study of P/e, the highest average heat transfer coefficient was recorded at 34.2 kW/m^2·K. The results indicated that the variation in P/e ratio seemed to have small effect on h values in laminar flow and insignificant effect at the non-laminar flow. At Re≈ 1300, the difference between highest and lowest h was around 3.1 kW/m^2·K while at Re≈ 4500, the difference dropped to 0.4 kW/m^2·K.